Field reports, Babs and Loren Padelford, summer 1990 - Padelford, Babset al; Padelford, Lorenet al (1990)
Field reports submitted by Babs and Loren Padelford for the summer 1990 with descriptions of some birds and handwritten notes. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1990. Epson - sheet feed/flatbed